Implikasi Gerakan Gulen Turki Terhadap Sistem Pendidikan di Jerman - Nabila Safitri; Gonda Yumitro (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2022)
This article discusses the implications of the Gulen Movement toward the education system in Germany. This research used a descriptive method to describe a phenomenon. This study was a qualitative research technique that analyzes data based on text and images. Data collection uses library research techniques or literature studies from various sources, namely journals, books, and news portals. Data or journals collection used Publish or Perish. The Gulen movement is spread across many countries. This research focuses on Germany and its implications on the education system in Germany. The results of this study are that Gulen-based schools in Germany does not have full implications for the education system in Germany, but they are easily accepted because they have the same educational value.